Clinical and functional remission assessment in patients with recurrent depression - N. N. Petrova (Неврология, нейропсихиатрия, психосоматика, 2019)
Objective: to make a clinical-scale assessment of remission in patients with recurrent depression. Patients and methods. The clinical and functional characteristics of remission were investigated in 121 patients with recurrent depression. The investigators used the following tests: the Montgomery-Asberg Depression Rating Scale (MADRS), the Brief Assessment of Cognition in Affective Disorders (BAC-A), the WHO Disability Assessment Schedule 2.0 (WHODAS 2.0), and the 36-item Short Form Health Survey (SF-36) questionnaire. They systematized remission, by identifying its four types: asymptomatic, that with asthenic symptoms, that with anxiety symptoms, hypothymic. Results and discussion. The criteria for complete remission with its average duration of 6 months were met in 58.6% of patients. Impaired social functioning was observed in all patients in remission. The predictors of incomplete remission were a family history; male gender; complex pattern of depression; and the presence of comorbid anxiety. The anxious variant of incomplete remission predominated, suggesting that it is advisable to choose anxiolytic antidepressants for maintenance therapy. New-generation antidepressant therapy is more frequently associated with complete remission. Whether therapy with different antidepressants might achieve functional remission was studied using agomelatine as an example. Conclusion. When assessing the results of treatment for depression, it is necessary to take into account not only clinical changes, but also social functioning in patients and, as a target of therapy to identify positive affect as one of the psychological parameters of quality of life. When choosing an antidepressant for the maintenance therapy of recurrent depression, its positive efficacy on the social functioning of patients should be an important criterion.